AI in the second language classrooms: enhancing Spanish writing skills with Copilot in a Danish university context - Morollon Marti, Natalia; Ángel-Cruz Burguillo , Gonzalo (Sprogforum. Tidsskrift for sprog- og kulturpædagogik, 2025)
The aim of this article is to show how to include the use of AI in the foreign language writing classroom as a tool to support learners in enhancing their language skills and it addresses the increasing interest in the use of AI-driven technologies and their potential in the language learning process. Specifically, this paper investigates the way in which a small group of Danish students of Spanish at university level engaged with Copilot to improve their written assignment of writing a blog post.